(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This text argues that in contemporary social systems, especially in those where raw multinational capitalism, systemic network consumption is dominant, there inhabits a pastiche schizoid / paranoid mode, whose design is to register and then challenge, in a piecemeal fashion, the subject become consumer, desiring a productive term objectified in joy, as an ephemeral mask of happiness. It is the integration pattern that is woven into that subject which inhabits contemporary social systems. In this climate, where daily life becomes "crazy", and where the norm is the destabilization of the few normal / pathological couples, the subject becomes a "crazy" consumer in an imperative machinistic logic of capitalist productivity.